Gender Differences in Concerns About Participating in Cancer Research During the COVID-19 Pandemic. (22nd January 2021) - Fox, Louis; Wylie, Harriet; Cahill, Fee; Haire, Anna; Green, Saran; Kibaru, Joyce; Hartley, Catherine; Sullivan, Richard; Van Hemelrijck, Mieke
Introduction: The ongoing SARS-CoV-2 pandemic is having major effects on cancer research, including major reductions in participant accrual to cancer clinical trials. Existing research has indicated that these steep drops in accrual rates to cancer clinical trials may be disproportionately affecting women. We sought to determine if there were gender differences in a dataset collected to examine participants' concerns about taking part in cancer research during the pandemic. Methods: Between 5-19 June 2020, we distributed a fully anonymized survey via social media. We contacted 85 UK cancer patient organizations/charities and asked them to share our questionnaire on their platforms, of which 26 obliged. Patients aged 18 with a cancer diagnosis were eligible to participate and asked about their clinical and demographic characteristics, concerns about research participation given the COVID-19 pandemic, anxiety levels measured using the Generalized Anxiety Disorder-7 (GAD-7) scale, amongst other questions. Anxiety levels and concerns about participating were compared between men and women using univariate and multivariate analyses. Results: 93 individuals, comprising n = 37 women and n = 56 men of various cancer types, provided survey responses. Independent t-tests showed that women reported higher anxiety scores, and concerns about participating in cancer research during COVID-19, than men. Linear regression analyses showed that anxiety scores predicted concerns about research participation in women but not men (pinteraction = 0.002). Conclusions: Cancer patients have concerns about participating in research during the COVID-19 pandemic that range from mild to serious. Furthermore, the relationship between general anxiety and concerns about research participation may be both more relevant and more pronounced in women than in men. Future work should examine the reasons why women are less likely to enrol in cancer trials during the COVID-19 pandemic.